Synthesis and Characterization of Fe3O4-Bentonite Nanocomposite Adsorbent for Cr(VI) Removal from Water Solution - Ngusey Adisu; Subramanian Balakrishnan; Haimanot Tibebe (International Journal of Chemical Engineering)
Bentonite-magnetite nanocomposite adsorbent (BMNC) was made and investigated for its adsorption removal of Cr(VI) from an aqueous solution. This adsorbent was prepared by the coprecipitation method from sodium bentonite (BNa) with iron chloride solution at controlled pH and under an inert atmosphere. These adsorbents were characterized by atomic absorption spectrophotometer (AAS), Brunauer–Emmett–Teller (BET), dynamic light scattering (DLS), scanning electron microscope (SEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD) analyses. Particle size of BMNC was in the range of 15 to 95 nm as per DLS. The intercalation of magnetite nanoparticles onto the bentonite clay increased its specific surface area from 142 to 177 m2/g as per BET analysis. Experimental design optimization results in 96.5% of Cr(VI) removal from the water solution at optimized adsorption parameters viz., adsorption time of 101 min, pH of 1.95, adsorbent dose of 1.12 g/L, and initial Cr(VI) concentration of 36.2 mg/L. The results of these studies demonstrate that the BMNC performs well. Moreover, the adsorption of Cr(VI) onto the BMNC was found to be the best fit with Langmuir isotherm (R2 = 0.9984) and a maximum adsorption capacity of 98 mg/g. The kinetics of the adsorption process was found to be a pseudo-second-order model (R2 = 0.9912). The BMNC also showed favourable reusability for adsorbate Cr(VI) ions removal from the water solution.